PENGARUH PEMBELAJARAN MENGGUNAKAN FACEBOOK TERHADAP KEMAMPUAN MENGENAL MASALAH KEPERAWATAN PASIEN KANKER PADA MAHASISWA KEPERAWATAN UNIVERSITAS UDAYANA - Ni Putu Intan Nanda Rista Putri; Putu Oka Yuli Nurhesti; I Ketut Suardana (Coping: Community of Publishing in Nursing, 2015)
Cancer is a disease that is characterized by abnormal growth of body cells. There is huge challenge for controlling cancer both in the world an Indonesia. Health care providers have important role to prevent the morbidity and mortality related cancer. It can be well they prepared when they are students. Nursing students should have good learning media for learning about cancer care. Facebook can be one option for this purpose. The aim of the study was to determine the effect of learning using Facebook to recognize the ability of nursing student to understand the nursing problems of patient with cancer. The method used quasi experimental approach with one group pre-post test design with simple random sampling technique. Data analyzed by Wilcoxon Signed Rank Test. This study was conducted on May, 18-31th 2015 at 68 nursing students of fourth semester in Udayana University. Results of this study found that the mean of pretest is 38,74, and posttest is 75,62, and the statistical analysis shown p value = 0.000 ( p < 0.05 ) or it can be concluded that there is a significant effect of learning using using Facebook to recognize the ability of nursing problem patients with in nursing student Udayana University.